Optimizing data quality in big data through unsupervised record linkage techniques - Bendida, Aissam; Djamel, Amar Bensaber; Adjoudj, Réda; Atig, Yahia (Edelweiss Applied Science and Technology, 2025)
In today's era of Big Data, maintaining high-quality data is crucial for effective data management. One key aspect of this is record linkage, which involves identifying, comparing, and merging records from different sources that refer to the same real-world entity. However, traditional record linkage methods struggle to keep up with the rapidly increasing volume and diversity of data. These methods often rely on labeled data, which can be expensive and difficult to obtain. To overcome these challenges, unsupervised blocking techniques have emerged as a promising alternative, allowing large-scale datasets to be managed efficiently without the need for pre-labeled data. In this article, we introduce a novel approach that integrates the Firefly Algorithm for optimized feature selection, Locality-Sensitive Hashing (LSH) for dimensionality reduction, and Length-based Feature Weighting (LFW) for improved data representation. Our methodology aims to enhance both the accuracy and scalability of record linkage in Big Data environments. Experimental results show that our approach is highly effective, demonstrating its potential to significantly improve data quality in large-scale datasets.